Pengaruh Penambahan Selulosa Kulit Nipah (Nypa fruticans) terhadap Karakteristik Smart Packaging Berbasis Pati – Kitosan - Nina Hartati; Tiara Andriani; Edi Kurniawan; Herlin Sumarna (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The development of environmentally friendly packaging materials with the ability to monitor food quality has become an important focus in biomass-based innovations. This study aims to develop bioplastic films based on durian seed starch–chitosan reinforced with cellulose from nipa palm husk and functionalized as smart packaging by incorporating Coleus scutellarioides (miana) extract as a natural indicator. The films were prepared using the solution casting method with varying starch-to-chitosan ratios (2:8, 4:6, 6:4, and 8:2) and cellulose additions (1 g, 3 g, and 5 g). Characterization included tensile strength, elongation at break, Young’s modulus, Water Vapor Permeability (WVP), Water Vapor Transmission Rate (WVTR), and sensitivity to meat quality. The results showed that the highest tensile strength (10.718 MPa) was obtained at the 2:8 ratio with 1 g cellulose, while the highest elongation (3.49%) was observed at the 8:2 ratio. The maximum Young’s modulus (9.40 MPa) was achieved at the 4:6 ratio with 1 g cellulose. The lowest WVP and WVTR values were found at the 6:4 ratio with 3 g cellulose, indicating improved barrier properties. The anthocyanins in miana extract exhibited a clear color response to pH changes, with prolonged storage leading to a shift toward acidic conditions. Overall, the optimal addition of cellulose enhanced mechanical and barrier properties, whereas excessive amounts led to agglomeration and reduced performance. These findings demonstrate the potential of combining durian seed starch, chitosan, cellulose, and miana extract as a biodegradable smart packaging material.